Analisis Prosedur Pelayanan Pembayaran Pensiun Pegawai Negeri Sipil (PNS) DI PT.TASPEN (PERSERO) Cabang Pematangsiantar - Richard Berlien; Eka Pratiwi Septania Parapat; Rico Pratama (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2020)
This study aims to determine how the civil servant pension payment service procedures and what obstacles are faced in the pension payment service and how to overcome them. This type of research is qualitative. The data collection techniques used were observation, interview and documentation. Data analysis techniques using data reduction, data presentation, and conclusions. The results showed that the service procedures for civil servants' pension payments were filing, verification, authorization, closing and posting. The problems faced are the existence of a family principle in the process of settling pension payment services and a deviation from standard operating procedures. This can be overcome by conducting training for employees to follow standard operating procedures and be subject to sanctions.